The Effect of Quantum Learning Model With Big Book Media on Reading and Writing Skills - Arif Kamaluddin; Rusnilawati (Jurnal Ilmiah Sekolah Dasar, 2022)
Reading and writing are very important skills in education. When compared to other countries, the ability to read and write Indonesian people is still low. This study aims to analyze whether the application of the Quantum Learning model with Big Book media can overcome the lack of reading and writing skills. The research design used was a quasi-experimental design. Where the two elementary schools were divided into an experimental class and a control class. Respondents in this study consisted of teachers and second grade students. Data collection techniques used are observation, tests, and documentation. The data analysis techniques used the normality test, homogeneity test, T test, and ANOVA test. The results showed that there was a significant increase in the posttest results of students' reading and writing skills after applying learning with the Quantum Learning model and Big Book media. The results of the ANOVA test showed that learning in the experimental class and control class could improve students' reading and writing skills, although the average value of the increase in the experimental class that applied the Quantum Learning model with Big Book media was higher.